Management Analysis of Green Open Spaces in the Urban Area of Kalabahi - Suhirman PANARA; Nursalam NURSALAM; Wenseslaus GAMPUR (Loka: Journal Of Environmental Sciences, 2023)
Purpose - The existence of green open spaces in the urban area of Kalabahi still requires the availability of land to achieve the target of at least 20% according to the mandate of Law Number 26 of 2007 concerning Spatial Planning and Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 1 of 2007 concerning Arrangement of Green Open Spaces in Urban Areas.Methodology - This study aims to analyze the functions of green open space management in the urban area of Kalabahi, which includes planning, organizing, implementing, and controlling, as well as analyzing the inhibiting factors of these management functions.Findings - This study used a qualitative research method located at the Alor Regency Public Works and Spatial Planning Office, the Alor Regency Tourism Office, and the Alor Regency Environmental Service. It was studied using the Miles and Huberman analysis technique.Implication - This study found that managing green open spaces in the urban area of Kalabahi has yet to run optimally. This is due to the ineffectiveness of the OPDs managing green open spaces in Alor Regency in carrying out their management functions for green open spaces in the urban area of Kalabahi.